Resilience to audiogenic seizures is associated with p-ERK1/2 dephosphorylation in the subiculum of Fmr1 knockout mice - Curia, Giulia; Gualtieri, Fabio; Bartolomeo, Regina; Vezzali, Riccardo; Biagini, Giuseppe (Frontiers in Cellular Neuroscience, 2013)
Young, but not adult, Fmr1 knockout (KO) mice display audiogenic seizures (AGS) that can be prevented by inhibiting extracellular signal-regulated kinases 1/2 (ERK1/2) phosphorylation. In order to identify the cerebral regions involved in these phenomena, we characterized the response to AGS in Fmr1 KO mice and wild type (WT) controls at postnatal day (P) 45 and P90. To characterize the diverse response to AGS in various cerebral regions, we evaluated the activity markers FosB/ΔFosB and phosphorylated ERK1/2 (p-ERK1/2). Wild running (100% of tested mice) followed by clonic/tonic seizures (30%) were observed in P45 Fmr1 KO mice, but not in WT mice. In P90 Fmr1 KO mice, wild running was only present in 25% of tested animals. Basal FosB/ΔFosB immunoreactivity was higher (P<0.01 vs WT) in the CA1 and subiculum of P45 Fmr1 KO mice. Following the AGS test, FosB/ΔFosB expression consistently increased in most of the analyzed regions in both groups at P45, but not at P90. Interestingly, FosB/ΔFosB immunoreactivity was significantly higher in P45 Fmr1 KO mice in the medial geniculate body (P<0.05 vs WT) and CA3 (P<0.01). Neurons presenting with immunopositivity to p-ERK1/2 were more abundant in the subiculum of Fmr1 KO mice in control condition (P<0.05 vs WT, in both age groups). In this region, p-ERK1/2-immunopositive cells significantly decreased (-75%, P<0.01) in P90 Fmr1 KO mice exposed to the AGS test, but no changes were found in P45 mice or in other brain regions. In both age groups of WT mice, p-ERK1/2-immunopositive cells increased in the subiculum after exposure to the acoustic test. Our findings illustrate that FosB/ΔFosB markers are overexpressed in the medial geniculate body and CA3 in Fmr1 KO mice experiencing AGS, and that p-ERK1/2 is markedly decreased in the subiculum of Fmr1 KO mice resistant to AGS induction. These findings suggest that resilience to AGS is associated with dephosphorylation of p-ERK1/2 in the subiculum of mature Fmr1 KO mice.